Effect of sodium hydroxide concentration in synthesizing zinc selenide/graphene oxide composite via microwave-assisted hydrothermal method - Lee, Han Kee; Talib, Zainal Abidin; Mamat @ Mat Nazir, Md Shuhazlly; Wang, Enze; Lim, Hong Ngee; Mahdi, Mohd Adzir; Ng, Eng Khoon; Mohd Yusoff, Norita; Al-Jumaili, Batool Eneaze; Liew, Josephine Ying Chyi (MDPI, 2019)
The effect of NaOH solution on the formation of nanoparticles has been the subject of ongoing debate in selenium-based material research. In this project, the robust correlation between the mechanistic growth of zinc selenide/graphene oxide (ZnSe/GO) composite and the concentration of NaOH are elucidated. The ZnSe/GO composite was synthesized via microwave-assisted hydrothermal method and the concentrations of NaOH are controlled at 2 M, 3 M, 4 M, 5 M and 6 M. The XRD spectra show that the crystal phases of the samples exhibited a 100% purity of ZnSe when the concentration of sodium hydroxide (NaOH) was set at 4 M. The further increase of NaOH concentration leads to the formation of impurities. This result reflects the essential role of hydroxyl ions in modifying the purity state of ZnSe/GO composite. The optical band gap energy of ZnSe/GO composite also decreased from 2.68 eV to 2.64 eV when the concentration of NaOH increased from 2 M to 4 M. Therefore, it can be concluded that the optimum concentration of NaOH used in synthesizing ZnSe/GO composite is 4 M. This project provides an alternative green method in the formation of a high purity ZnSe/GO composite.